Implementation of the Three-Language Pocket Dictionary (Indonesian, English, and Mandarin) for Students of the Tourism Business Program at Makassar Tourism Polytechnic - Azizah, Mirah; Marsuki, Ria Riski; Riski, Hasria (Universitas Negeri Semarang, 2024)
This study discusses the role of language in everyday communication and the development ofTourism Polytechnic as educational institutions that also incorporate the teaching of variousforeign languages. The research was conducted at the Makassar Tourism Polytechnic. Thisinstitution places significant emphasis on the study of Tourism, especially hospitality andlanguages, including Mandarin and English.The goal of implementing this two-language dictionary is to help respondents quickly expand their vocabulary for use in tourism communication, according to their preferred language fields. This study uses a quantitative method with a comparative design. The instruments used were observation, pretest, and posttest, conducted with 50 students.The results showed a significant improvement in the mastery of foreign language vocabulary,particularly in Mandarin and English. A SWOT analysis was then conducted on the twolanguage pocket dictionary, highlighting its strengths, weaknesses, opportunities, and threats.The article also presents comparative graphs of pretest, middle test, and posttest results for English, and Mandarin.The findings suggest that the implementation of the two-language dictionary at MakassarTourism Polytechnic successfully improved the foreign language vocabulary mastery of students.